Mortarboard Review: Montessori-Related Dissertations, 2023 - Parham, Joel; Moss, Jennifer; Keller Wood, Katie (Journal of Montessori Research, 2024)
This is the second article in an ongoing series, published annually, highlighting a selection of English-language dissertations from the previous calendar year related to Montessori philosophy and education. Thirteen doctoral dissertations completed and approved during the 2023 calendar year were identified. The authors selected three dissertations to spotlight because they represent high-quality research in an area that is relevant to the current educational landscape: antibias and anti-racist (ABAR) educational practices.